Pediatric to adult‐care transitions in childhood‐onset chronic disease: Hospitalist perspectives. Issue 11 (12th October 2013) - Hunt, Susan; Sharma, Niraj
Abstract : OBJECTIVE: Survey of adult‐centered hospitalist perspectives on caring for adults with chronic diseases of childhood onset (CDoCO) to investigate comfort level and identify targets of future educational and policy intervention. METHODS: We developed an on‐line survey for adult‐centered hospitalists based on a prior outpatient survey and introduced it to the Society of Hospital Medicine membership via e‐mail. Consent was implied by completing the survey. RESULTS: Of all respondents, 60% saw 5 or more adults with CDoCO over a 6‐month period. Among internal medicine respondents, 40% did not feel comfortable caring for this population, with lack of familiarity with the literature, lack of training in CDoCO, coordinating with multiple specialists, and lack of training in adolescent development and behavior ranked as the most significant barriers to care. CONCLUSION: The steadily growing population of adults with CDoCO and their high inpatient utilization have lead to increased care by adult‐centered hospitalists, many of whom do not feel comfortable caring for them. Educational initiatives aimed at increasing medical knowledge base for common issues, training in adolescent development, increased care coordination, and access to address psychosocial issues would improve hospitalist comfort and patient care for this vulnerable population. Journal of Hospital Medicine 2013;8:627–630. © 2013 Society of Hospital Medicine